Tarbiyyah Ruhiyyah and Deviant Behavior in Islamic Schools: An Empirical Sem-Based Study - Basri, Hasan; Muslikhin; Maulana, Rizka Husnu; Aqil Baihaqi, Mohammad (Jurnal Ilmiah Peuradeun, 2026)
Deviant behavior among students continues to challenge value-based educational institutions, raising concerns about the effectiveness of spirituality-oriented education in shaping moral self-regulation. This study investigates the role of tarbiyyah ruhiyyah as an internalized spiritual education model in reducing deviant behavior among Islamic secondary school students, with particular emphasis on the differential effects of its core dimensions. Using a quantitative design, survey data were collected from 120 students at a formal Islamic school in Indonesia and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that spiritually internalized dimensions—namely, individual spiritual strengthening, interaction with the Qur’an, mentoring and moral coaching, and awareness of tazkiyatun nafs—significantly reduce deviant behavior. In contrast, routine religious practices performed without reflective depth show no significant behavioral effect. These results demonstrate that spirituality contributes to moral regulation only when it operates as an internalized, reflective, and relational process rather than as ritual compliance. The study advances moral and character education theory by empirically distinguishing transformative spirituality from ritualistic religiosity and offers practical insights for designing spirituality-based character education programs applicable across diverse cultural and educational contexts.